Preparation of a Sunitinib loaded microemulsion for ocular delivery and evaluation for the treatment of corneal neovascularization in vitro and in vivo - Shi, Jieran; Yang, Jingjing; Xu, Haohang; Luo, Qing; Sun, Jun; Zhang, Yali; Liang, Zhen; Zhao, Ningmin; Zhang, Junjie (Frontiers in Pharmacology, 2023)
Background: Corneal neovascularization (CNV) is a pathological condition that can disrupt corneal transparency, thus harming visual acuity. However, there is no effective drug to treat CNV. Sunitinib (STB), a small-molecule multiple receptor tyrosine kinase inhibitor, was shown to have an effect on CNV. The purpose of this study was to develop an STB microemulsion (STB-ME) eye drop to inhibit CNV by topical application. Methods: We successfully prepared an STB-ME by the phase inversion emulsification method, and the physicochemical properties of STB-MEs were investigated. The short-term storage stability, cytotoxicity to human corneal epithelial cells, drug release, ocular irritation, ocular pharmacokinetics and the inhibitory effect on CNV were evaluated in vitro and in vivo. Results: The optimal formulation of STB-ME is composed of oleic acid, CRH 40, Transcutol P, water and sodium hyaluronate (SH). It is a uniform spherical particle with a mean droplet size of 18.74 ± 0.09 nm and a polydispersity index of 0.196 ± 0.004. In the in vitro drug release results, STB-ME showed sustained release and was best fitted by a Korsmeyer-Peppas model (R2 = 0.9960). The results of the ocular pharmacokinetics in rabbits showed that the formulation containing SH increased the bioavailability in the cornea (2.47-fold) and conjunctiva (2.14-fold). STB-ME (0.05% and 0.1%), administered topically, suppressed alkali burn-induced CNV in mice more effectively than saline, and high-dose (0.1%) STB-ME had similar efficacy to dexamethasone (0.025%). Conclusion: This study provides a promising formulation of STB-ME for the inhibition of CNV by topical administration, which has the excellent characteristics of effectiveness, sustained release and high ocular bioavailability.